The effect of size on the plastic deformation of annealed cast aluminium microwires. (1st March 2019) - Verheyden, S.; Pires Da Veiga, L.; Deillon, L.; Mortensen, A.
Abstract: Monocrystalline, cast aluminium microwires of diameter ( D ) below 25 μm free of micromilling artefacts are annealed under protective atmosphere. Annealing increases the flow stress of all tested microwires, by an amount that is found, in a Haasen plot of measured activation area values, to be an athermal contribution to the flow stress that is attributed to surface oxide layer thickening. Microwires oriented for single slip with D 14 μm behave as do as-cast microwires with D 7 μm, showing a transition to higher and more stochastic flow stress values; this effect is attributed to a greater scarcity of dislocation sources after annealing. Graphical abstract: